Effect of tissue staining in quantitative phase imaging. Issue 8 (31st May 2018) - Ban, Sungbea; Min, Eunjung; Ahn, Yujin; Popescu, Gabriel; Jung, Woonggyu
Abstract : Quantitative phase imaging (QPI) is an emerging modality, which enables the identification of abnormalities in tissue based on optical properties. QPI can be applied to any biological specimen due to its label‐free imaging capability, but its use in stained tissue is unclear. Here, we study the variability of QPI with the staining dye. Several tissues such as brain, heart and lung were stained with hematoxylin and eosin, and their optical properties compared at 550 and 730 nm. Our results showed that phase and scattering coefficients varied when QPI was used at the absorption wavelength of the staining dye. We also found that the variation of optical properties was dependent on tissue morphology. Abstract : Wide‐field phase delay of mouse brain slice obtained by quantitative phase imaging in different wavelength and various pinhole size, from which it retrieves power spectrum in corpus callosum, scattering coefficient ( μ s ) and anisotropy (g).